The Female Gaze in Hind Bensari’s “475 Break the Silence”: A Social Activist and Feminist Account - Omar, Maabich (Technium Education and Humanities, 2025)
This study explores the concept of the “female gaze” in Hind Bensari’s “475 Break the Silence (2014)”. The focus of this work targets aspects of the “female gaze” like the documentarian’s use of subjectivity, identification, intimacy, and other features such as close-up shots, narrative structure, and polyphonic voices to address feminist issues which include rape, violence, gender roles, discrimination, the loophole of the Article 475 from the Moroccan Penal Code, the limitations of Mudawana (Family Code/Reform) and its legal, social, cultural impacts on Moroccan women. The notion of the “female gaze”, which is developed by Lisa French (2021), offers an impactful perspective through which female documentarians and filmmakers address feminist issues in their films. The article also highlights how these aspects of the “female gaze” offer empowerment and agency for victims of rape and violence to critique the perpetuation and the normalization of the Moroccan culture and society with such patriarchal and discriminating acts and crimes. The study concludes by revealing how the director has created an emotional bound between the documentarian, the victims of rape, and the audience that will sensitize about the legal, social, and cultural discrimination and injustice of these victims, call for action and social activism to put an end of these sufferings and traumas that the survivors and victims of rape are experiencing.